"For lack of accountability": The logic of the price in Ireland's Magdalen Laundries. (May 2015) - Killian, Sheila
Abstract: Ireland's Magdalen Laundries are now infamous for the damaging impact they had on the lives of the women who passed through them throughout the twentieth century. The relationship between the state and the Laundries was constituted using a deliberately informal frame characterised by an excision of the " logic of the price ". This wilful disregard for the economic was significant in form and function, and was mirrored within the institutions where the women were "accounted for" in ways that rendered "accounting to" them unthinkable. The Laundries functioned for the emerging Irish state as a tool that helped to orchestrate a shared national habitus and to moderate the state's own account of the role and record of women. The way in which the relationship between the state and the institutions was constructed almost 100 years ago continues to mute accountability and to serve the interests of power. The closed nature of the institutions now permits an examination of the impact of this deliberate informality. This reveals the potentially devastating consequences of the removal of accounting ways of thinking from relationships between the state and private bodies to which pivotal services have been outsourced. Analysis of the case using a Bourdieusian frame has implications for accounting as a discipline in public contexts and for the way in which we understand the limits of state responsibility in the case of outsourced or privatised service provision and policy formation.